Shale swelling mitigation in water-based drilling fluids with amine additives - Ismail, Abdul Razak (2015)
Shale stability is a common problem in wellbores when water based drilling fluids are used during drilling operations. The high reactivity of shales with water causes clay components to swell and cause many drilling problems. Potassium chloride has been the most conventional shale stabilizer additive used in water based drilling fluid. However there are limitations to the ability of KCl. The swell-preventing ability of KCl does not last long in water based drilling fluid. Amines are stated to have better inhibition longevity in water based drilling fluid. This study investigated the efficiency of amines as shale stabilizers in mitigating shale swelling, and compared its performancdrill with KCl. An amine compound, hexamethylene diamine (HMDA) was used in this study. Drilling fluid samples were tested on 15 mm thick compacted shale pellets with high amounts of montmorillonite. Concentration tests showed that drilling fluid with 2.85 - 3.4 % (10 - 12 g) of HMDA gave optimum swelling mitigation; three times less swelling than 30 g of KCl. The shale immersed in HMDA showed swelling of less than 8 % of its original size, as compared to KCl, which had 22 %. The shales submerged in HMDA showed also slower rates of swelling than those in KCl. An extended experiment termed the ‘Inhibition Longevity Test’ was carried out on each sample to test the robustness of the swell-mitigation effect of the drilling fluid upon the shale; water was subsequently added to each ongoing swelling experiment. HMDA was able to maintain its swelling-mitigation ability, allowing only an added 1 % swelling increment. KCl was however weaker in holding its swelling-prevention effect, resulting in an additional 5 % of swelling of its shale. It appears that amine bonds are broken less easily. The chemical structure which makes up amines create stronger bonds between shale particles, effectively inhibiting swelling. It is concluded that amines are more efficient shale-stabilizer additives compared to KCl.